PELATIHAN PERTOLONGAN PERTAMA PADA KECELAKAAN LALU LINTAS METODE AUDIO VISUAL TERHADAP PENGETAHUAN PEMUDA KARANG TARUNA - Nanda Wira Saputri; Dwiharini Puspitaningsih; Yudha Laga Hadi Kusuma (MEDICA MAJAPAHIT, 2023)
Quick first aid is very important for victims to anticipate the severity of further injuries. Providing first aid training in traffic accidents can increase knowledge to help correctly and appropriately. The purpose of this study was to determine the effect of providing first aid training on traffic accidents with the audiovisual method to youth organizations awareness in Bareng villange Sumberejo Pandaan Pasuruan. This study used pre-experimental research method with the one-group pre-post test design. The population in this study were the youth organizations in Bareng villange Sumberejo as many as 52 people. The sampling technique is using the simple random sampling of 46 samples. Data analysis using the Wilcoxon Signed Ranks Test results in p value = 0.000 with alpha level of α = 0.05, which means there is a difference before and after being given first aid training in traffic accidents with the audiovisual method to youths awareness. The results of this study was should that there is an improvement knowledge from the respondens regarding the first aid on traffic accidents Most of the respondents have great awareness about first aid in traffic accidents